2008
DOI: 10.2118/08-11-56
|View full text |Cite
|
Sign up to set email alerts
|

Clarifications on Oil/Heavy Oil Recovery Under Ultrasonic Radiation Through Core and 2D Visualization Experiments

Abstract: Our previous research on the effects of ultrasonic waves on oil recovery conducted at the University of Alberta had shown that capillarity and interfacial tension (IFT) might be responsible for the observed improvements in incremental oil recovery. Although the results seem encouraging, questions about the mechanism and effective parameters causing additional recovery still remain. To analyze the influence of parameters other than IFT and capillary forces, we conducted capillary imbibition ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Similar investigations have been conducted by Naderi and Babadagli [21] on some sandstone core samples with different wettabilities under ultrasound. They concluded that ultrasound effect on oil recovery is more significant in the oil-wet case and recovery rate as well as ultimate recovery for heavier oil is trivial compared to the lighter oil.…”
Section: Introductionsupporting
confidence: 77%
“…Similar investigations have been conducted by Naderi and Babadagli [21] on some sandstone core samples with different wettabilities under ultrasound. They concluded that ultrasound effect on oil recovery is more significant in the oil-wet case and recovery rate as well as ultimate recovery for heavier oil is trivial compared to the lighter oil.…”
Section: Introductionsupporting
confidence: 77%
“…To change the wettability of the micromodel, which was originally water wet (WW), a siliconizing fluid (SurfaSil TM ; chemical composition is primarily dichlorooctamethyltetrasiloxane) was used to coat the glass surface (Shabani et al, 2009(Shabani et al, , 2010Naderi and Babadagli, 2008). SurfaSil TM works by reacting directly with polar groups (silanols) on the glass surface.…”
Section: Wettability Alterationmentioning
confidence: 99%
“…A more critical factor is the interfacial forces and ultrasonic energy expected to significantly affect these forces and fluid-fluid and fluid-rock interaction (Hilpert et al 2000;Hamida & Babadagli 2005, 2007a, b, 2008aNaderi & Babadagli 2008a, b, 2010. Wettability of the medium and IFT between oil and water are critical properties to be influenced by ultrasonic waves and cause changes in the displacement patterns in porous media (Hamida & Babadagli 2008a).…”
Section: 2mentioning
confidence: 99%
“…As a continuation of this research, Naderi & Babadagli (2008a, b, 2010 performed experiments to analyse the effects of ultrasonic waves on oil recovery out of consolidated sandstone cores and unconsolidated glass bead models. They also analysed the displacement patterns while injecting water to displace different viscosity oils in water-wet 2D glass bead models (Naderi & Babadagli 2008a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation